Learning Smart Farming through IoT Prototypes, Educational Impacts of Smart Goat Housing Systems in Vocational Education - Achmad Tavip Junaedi; Nicholas Renaldo; Wilda Susanti; Rangga Rahmadian Yuliendi; Wahyu Joni Kurniawan; Yulvia Nora Marlim; Kristy Veronica; Harry Patuan Panjaitan; Umar Faruq; Jahrizal Jahrizal (Reflection: Education and Pedagogical Insights, 2026)
This study investigates the educational impacts of learning smart farming through Internet of Things (IoT)-based smart goat housing systems in vocational education. The rapid digital transformation of agriculture has created a growing demand for graduates with strong technological and applied competencies; however, the integration of real smart farming technologies into vocational curricula remains limited. To address this gap, this research employed a quasi-experimental design with a pretest–posttest non-equivalent control group to compare IoT prototype-based learning with conventional instructional approaches. The study involved vocational students enrolled in agriculture-related programs, where the experimental group engaged in project-based learning using an operational IoT-enabled smart goat housing system, while the control group received traditional instruction. The findings indicate that students exposed to IoT prototype-based learning demonstrated significantly higher improvements in digital competence, applied learning outcomes, and learning engagement compared to those in the control group. Qualitative insights further revealed that authentic interaction with real-time data and automated systems enhanced students’ understanding, motivation, and confidence in using digital technologies. These results highlight the pedagogical value of integrating real IoT prototypes into vocational education and confirm the effectiveness of experiential and technology-enhanced learning approaches in developing workforce-relevant competencies. This study contributes to vocational education literature by positioning livestock-based smart farming systems as effective learning media for digital agriculture education.